2005
DOI: 10.1530/eje.1.01999
|View full text |Cite
|
Sign up to set email alerts
|

Central administration of resistin promotes short-term satiety in rats

Abstract: Objective: Several hormones expressed in white adipose tissue influence food intake at the central level. We sought to determine whether resistin, a circulating adipose-derived hormone in rodents, has actions on the hypothalamus by determining the effects of central resistin injection on food intake and on hypothalamic Fos protein expression. Design: As resistin expression in adipose tissue is influenced by altered nutritional status, we studied the effect of central resistin in both fed and pre-fasted rats. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 17 publications
4
56
0
4
Order By: Relevance
“…ERK1/2-MAPK phosphorylation was only affected in rat GCs. Protein and mRNA expression of resistin have been described in several tissues of the reproductive axis (Morash et al 2002, Nogueiras et al 2004, Brown et al 2005, Tovar et al 2005. Furthermore, resistin mRNA is expressed in the bovine mammary gland, and its expression in this tissue decreases during lactation (Komatsu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK1/2-MAPK phosphorylation was only affected in rat GCs. Protein and mRNA expression of resistin have been described in several tissues of the reproductive axis (Morash et al 2002, Nogueiras et al 2004, Brown et al 2005, Tovar et al 2005. Furthermore, resistin mRNA is expressed in the bovine mammary gland, and its expression in this tissue decreases during lactation (Komatsu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of resistin (mRNA and protein) has been reported in several reproductive tissues including hypothalamus (Morash et al 2002, Tovar et al 2005, pituitary (Morash et al 2002, Brown et al 2005, and testis (Nogueiras et al 2004). In hypothalamus, resistin has been shown to inhibit feeding (Tovar et al 2005, Vazquez et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The resistin levels, however, were significantly higher in the HO group, suggesting that they may be raised due to mechanisms other than insulin resistance. The hypothalamic action of resistin is unclear, but animal studies have demonstrated that central administration of resistin reduces food intake in the short term (52,53). Resistin receptors are present within the hypothalamus, in particular the arcuate and ventromedial nuclei (53,52).…”
Section: Adiponectin and Resistinmentioning
confidence: 99%
“…We have found that loss of resistin in leptin-deficient mice exacerbates obesity by further decreasing energy expenditure, but insulin sensitivity is enhanced (R.S.A., unpublished data). Recent reports have described inhibition of food intake and induction of hepatic insulin resistance by intracerebroventricular resistin administration (90,91).…”
Section: Role Of Leptin In Famine and Feastmentioning
confidence: 99%